2017
DOI: 10.1080/09168451.2017.1390393
|View full text |Cite
|
Sign up to set email alerts
|

New triterpene saponins from the roots of Acacia macrostachya (Mimosaceae)

Abstract: Four new oleanane-type saponins, macrostachyaosides A, B, C, and D (1-4) were isolated from the roots of Acacia macrostachya. Their structures were elucidated on the basis of extensive 1D- and 2D-NMR data and HR-ESI-MS analyses. At concentrations of 100 μM of each compounds, none of the tested compounds caused a significant growth reduction against HL60 cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Acacia s.l. plant foods are likely interesting sources of new biologically active phytochemicals from these groups (i.e., cardiac glycosides, steroids, alkaloids, and saponins) (Kim et al, 2015;Lomarat et al, 2015;Rifai et al, 2010;Ruangsuriya et al, 2022;Tchoukoua et al, 2017Tchoukoua et al, , 2018Tezuka et al, 2000). Lectin activity, for instance, is rarely detected, and the reports (Balogun & Fetuga, 1989;Hapner & Jermyn, 1981;Lee et al, 1977;Rajaram & Janardhanan, 1991) present discrepancies, suggesting that Senegalia seeds have minor lectins or hemagglutination inhibitors (Hapner & Jermyn, 1981).…”
Section: Phytochemicals: Nutrients Bioactives or Antinutritional Fact...mentioning
confidence: 99%
See 1 more Smart Citation
“…Acacia s.l. plant foods are likely interesting sources of new biologically active phytochemicals from these groups (i.e., cardiac glycosides, steroids, alkaloids, and saponins) (Kim et al, 2015;Lomarat et al, 2015;Rifai et al, 2010;Ruangsuriya et al, 2022;Tchoukoua et al, 2017Tchoukoua et al, , 2018Tezuka et al, 2000). Lectin activity, for instance, is rarely detected, and the reports (Balogun & Fetuga, 1989;Hapner & Jermyn, 1981;Lee et al, 1977;Rajaram & Janardhanan, 1991) present discrepancies, suggesting that Senegalia seeds have minor lectins or hemagglutination inhibitors (Hapner & Jermyn, 1981).…”
Section: Phytochemicals: Nutrients Bioactives or Antinutritional Fact...mentioning
confidence: 99%
“…Acacia s.l. plant foods are likely potential sources of new biologically active phytochemicals (Kim et al, 2015;Lomarat et al, 2015;Rifai et al, 2010;Ruangsuriya et al, 2022;Tchoukoua et al, 2017Tchoukoua et al, , 2018Tezuka et al, 2000). Further research is needed to profile the phytochemicals from Acacia s.l.…”
Section: Safety Concerns Regarding the Food Use Of Senegalia Seedmentioning
confidence: 99%
“…Of note, investigations of leaf, stem, and root bark extracts of A. macrostachya revealed the presence of secondary metabolites, such as saponins, flavonoids, tannins, and alkaloid salts [ 13 , 15 ]. Furthermore, qualitative analyses of methanol extracts from the roots of this plant revealed the presence of triterpenes, steroids, and tannins [ 2 , 16 ]. The presence of these secondary metabolites could justify the antioxidant and anticancer properties [ 2 ] of this plant.…”
Section: Introductionmentioning
confidence: 99%
“…Previous biological activity studies have confirmed the anticancer [ 10 ], antidiabetic [ 11 ], antioxidant [ 12 ], anti-inflammatory, analgesic [ 13 ], antiplasmodial, [ 14 ] and antibacterial [ 15 ] activities of different parts of A. macrostachya . Other works report the presence of oleanane triterpene saponins in the roots as well as phenolic acids and flavonoids with antioxidant activity in the leafy stems [ 15 , 16 ]. In a continuing effort to investigate the bioactivities of tropical medicinal plants [ 17 , 18 ], the antibacterial, antibiofilm, and efflux pump inhibition activities of the stem of A. macrostachya (Leguminoseae) were studied.…”
Section: Introductionmentioning
confidence: 99%